Left subclavian artery stenosis treated with transcatheter stent placement in pediatric patients - Mahua Roy; Amitava Chattopadhyay; Biswajit Bandhyopadhyay; Debosree Gangopadhyay (Wolters Kluwer Medknow Publications, 2019)
Left subclavian artery (LSA) stenosis causing limb length shortening or vascular compromise or significant pulse volume and blood pressure differences between two upper limbs are rarely described in pediatric patients. Here, we are presenting three such cases, two of them were congenital and another one acquired in origin. All of them were successfully treated with transcatheter implantation of stent in LSA. Normalization of limb length was detected on follow-up.